2005
DOI: 10.1111/j.1468-0270.2005.00584.x
|View full text |Cite
|
Sign up to set email alerts
|

Planning by Commonhold

Abstract: So-called 'gated' communities have become common throughout the continents of Asia and America. Such communities are characterised by the ability to provide public goods and perform governance functions, independent of central and local government. It would be surprising if such communities did not develop to a greater extent in Britain, especially as a more complete legal framework now exists for their governance. Examples in Asia and America demonstrate their effectiveness, as do historical examples in the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…These have been applied to successfully generate the necessary incentives that encourage resource conservation and help overcome the problem of 'free riding' (Anderson & McChesney, 2003;Webster & Le Goix, 2005).…”
Section: Critiquementioning
confidence: 99%
“…These have been applied to successfully generate the necessary incentives that encourage resource conservation and help overcome the problem of 'free riding' (Anderson & McChesney, 2003;Webster & Le Goix, 2005).…”
Section: Critiquementioning
confidence: 99%
“…There is a diversity in the gated community phenomenon that does not always come out in the literature, as Sanchez and Lang's (2005) document using a nationwide sample of census data. In a follow-up study, data from the 2000 US Census show that gating seems to increase social and economic segregation (Le Goix 2005). A 2003 study of California showed that while most GCs are located within upper-or middle-class white areas, 20% are located within middle-and lower-income Asian or Hispanic neighbourhoods, which proliferate in the northern parts of Orange County and San Fernando Valley (Le Goix 2002Goix , 2003.…”
Section: Segregationmentioning
confidence: 99%
“…Contrary to popular conceptions, GCs are not solely composed of wealthy, white and retired residents; buyers of various classes seek to purchase homes in clubbed neighbourhoods. All else being equal, they are less likely to be segregated by race or ethnicity than other regions of the city (Le Goix 2003Goix , 2005. In a follow-up study, data from the 2000 US Census show that gating seems to increase social and economic segregation (Le Goix 2005).…”
Section: Segregationmentioning
confidence: 99%
“…By providing their own security, infrastructure and services, these developments reduce public financial responsibility while generating new fiscal revenues. Thus, the gated enclaves are instrumental in transferring the cost of urban sprawl from public authorities to private developers and homeowners and are popular and efficient planning tools in fast growing areas (McKenzie 1994;Ben-Joseph 2004;Le Goix 2005a;Webster and Le Goix 2005). A significant distinction between the traditional suburb and the GC is that GCs are concentrated in specific parts of the US, the southwest, and in several states: Florida, California, Arizona, and Nevada.…”
Section: Economic Residential Segregationmentioning
confidence: 98%